PERKEMBANGAN ESAI (AL – MAQOLAH) PADA PROSA ARAB MODREN - fuadi, khairul (Program Studi Bahasa dan Sastra Arab Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
Prose is a type of Arabic literature, the aim of which is to convey a writer's ideas and thoughts to the reader or audience. However, the prose is not tied to wazans and qofiyah, it looks like classic Arabic poetry. Prose has existed since the ignorant period and continues to develop into modern times. Through this long process, prose has developed according to its times, one of which is al maqolah (essay) which has developed in modern times. This development could not be separated from the western influence that dominated the Arab world at that time. This article will discuss how Arabic prose has developed in modern times by using bibliographic methods to investigate various sources of information related to problems.